The Effect of Travel Motivation, Perceived Risk and Travel Constraint Towards Medan Generation Z’s Visit Intention to Bali, Indonesia Specifically Kuta area Through Destination Image - Gracia Gracia; Ronald Ronald; Amelia Amelia (IPM2KPE, 2024)
In this study aims to determine and analyze travel motivation, travel motivation, perceived risk has a significant effect on cognitive image and affective image and visit intention. The research study used quantitative research design and data processing using Structural Equation Modeling (SEM) with AMOS 26.0 to analyze data collected from a total of 105 respondents. Data collection was conducted by nonprobability snowball sampling technique on male and female respondents aged 18-24 years domiciled in Medan. The results obtained that travel motivation has a significant effect on cognitive image, travel motivation has a significant effect on affective image, perceived risk has a significant effect on cognitive image, perceived risk has a significant effect on affective image, travel constraint has a significant effect on cognitive image and affective image, cognitive image and affective image has a significant effect on visit intention. The implications in the research provide valuable insights for the tourism industry in Kuta to develop effective marketing strategies to attract more potential visitors from Medan's Generation Z population.. Keyword: Affective Image, Destination Image, Cognitive Image, Travel Motivation